How to improve the physical health of people with severe mental illness? A multicentric randomized controlled trial on the efficacy of a lifestyle group intervention. Issue 1 (23rd November 2021) - Luciano, Mario; Sampogna, Gaia; Amore, Mario; Andriola, Ileana; Calcagno, Pietro; Carmassi, Claudia; Del Vecchio, Valeria; Dell'Osso, Liliana; Di Lorenzo, Giorgio; Gelao, Barbara; Giallonardo, Vincenzo; Rossi, Alessandro; et al.
Abstract: Background : People with severe mental illnesses (SMI) have a mortality rate two times higher compared to the general population, with a decade of years of life lost. In this randomized controlled trial (RCT), we assessed in a sample of people with bipolar disorder, major depressive disorder, and schizophrenia spectrum disorder, the efficacy of an innovative psychosocial group intervention compared to a brief psychoeducational group intervention on patients' body mass index (BMI), body weight, waist circumference, Framingham and HOMA-IR indexes. Methods : This is a multicentric RCT with blinded outcome assessments carried out in six Italian university centers. After recruitment patients were randomized to receive a 6-month psychosocial intervention to improve patients' physical health or a brief psychoeducational intervention. All recruited patients were assessed with standardized assessment instruments at baseline and after 6 months. Anthropometric parameters and blood samples have also been collected. Results : Four-hundred and two patients with a diagnosis of bipolar disorder (43.3%), schizophrenia or other psychotic disorder (29.9%), or major depression (26.9%) were randomly allocated to the experimental ( N  = 206) or the control group ( N  = 195). After 6 months, patients from the experimental group reported a significant reduction in BMI (odds ratio [OR]: 1.93, 95% confidence intervals [CI]: 1.31–2.84; p  < 0.001), body weight (OR = 4.78, 95% CI: 0.80–28.27, p  < 0.05), and waist circumference (OR = 5.43, 95% CI: 1.45–20.30, p  < 0.05). Participants with impaired cognitive and psychosocial functioning had a worse response to the intervention. Conclusions : The experimental group intervention was effective in improving the physical health in SMI patients. Further studies are needed to evaluate the feasibility of this intervention in real-world settings.